Ascites and epithelial ovarian cancers: a reappraisal with respect to different aspects. Issue 1 (1st January 2007) - Ayhan, A.; Gultekin, M.; Taskiran, C.; Dursun, P.; Firat, P.; Bozdag, G.; Celik, N. Y.; Yuce, K.
Abstract : Ascites is a common finding in patients with epithelial ovarian cancer (EOC). Clinico-pathologic correlations with respect to the presence of ascites, positive cytology and prognostic role of ascites, and the impact of ascitic volumes were not previously studied extensively. A total of 372 patients with EOC were retrospectively evaluated with respect to presence and amount of ascites, cytologic findings, and survival. Two groups were compared by using Chi-square, Student's t and Mann-Whitney U, binary logistic regression, Kaplan Meier and Cox-regression analysis tests, where appropriate. Omental metastasis ( P < 0.001; OR: 3.21, 95% CI = 1.945–5.297) and mean number of metastatic lymph nodes ( P = 0.008; OR: 1.063, 95% CI = 1.016–1.112) were significantly related with presence of ascites. Evaluation of ascitic volume at different thresholds revealed lymphatic-omental metastasis, and also the disease stage to be significantly different among patient groups at lower threshold values and the positive cytology and high-grade diseases at higher threshold values. In conclusion, presence of ascites correlates with both the intraperitoneal and also the retroperitoneal tumor spread. Amount of ascites has different correlations with the clinico-pathologic factors depending on the thresholds chosen. At lower volumes, lymphatic and omental metastasis seems to correlate with the development of ascites. Once ascites develops, tumor grade seems to be important for larger ascites volumes. Neither the presence of ascites or its volume nor the cytologic positivity was an independent predictor of survival.